2021
DOI: 10.1002/sd.2220
|View full text |Cite
|
Sign up to set email alerts
|

Towards poor‐centred value chain for sustainable development: A conceptual framework

Abstract: Value chain for development (VCD) has increasingly been promoted for poverty reduction; yet, there is inadequate evidence on its effectiveness. Based on a comprehensive literature review, this article offers reasons why evidence on VCD impacts on poverty reduction is uncertain. It also suggests a conceptual framework for the poor-centred value chain for sustainable development to guide a better analysis of VCD participation and poverty impacts. The framework is particularly useful for researchers involved in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Secondly, while the current literature linking interventions to wellbeing and equity impacts tends to focus on standards, further research is necessary to assess whether other types of trade interventions (e.g., multi-or bi-lateral trade agreements, tariffs, subsidies and taxes, non-tariff measures, rules of origin) as well as initiatives targeting smallholders directly (Terlau et al, 2019) or newly designed value chains (Minh & Osei-Amponsah, 2021. ) lead to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, while the current literature linking interventions to wellbeing and equity impacts tends to focus on standards, further research is necessary to assess whether other types of trade interventions (e.g., multi-or bi-lateral trade agreements, tariffs, subsidies and taxes, non-tariff measures, rules of origin) as well as initiatives targeting smallholders directly (Terlau et al, 2019) or newly designed value chains (Minh & Osei-Amponsah, 2021. ) lead to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A major sustainable development issue is that poverty rates among the producers of commodities such as coffee and cocoa, predominantly smallholder farmers in the Global South, continue to be high. These smallholders have difficulty accessing sustainable global value chains (GVCs) (Asamoah et al, 2013; Garrett et al, 2021; Minh & Osei‐Amponsah, 2021). A wide range of efforts to increase farmer prices and increase smallholder productivity and incomes exist (Birner & Resnick, 2010; Garrett & Rausch, 2016; Lima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2018) have concluded that a proper understanding of the transmission of credit risk in the SCF network is very important for a company. In order to have a responsive supply chain, supply chain design configuration and a proper SC strategy in place is essential (Minh & Osei‐Amponsah, 2021).…”
Section: Network Analysis Of Research Publicationsmentioning
confidence: 99%
“…have concluded that a proper understanding of the transmission of credit risk in the SCF network is very important for a company. In order to have a responsive supply chain, supply chain design configuration and a proper SC strategy in place is essential(Minh & Osei-Amponsah, 2021).Cluster 4: SCF process and modelling This cluster focuses mainly on the processes and modelling of SCF. Supply chain trade credit, information asymmetry, SCF modelling, SC finance flows and framework are highlighted in this cluster.…”
mentioning
confidence: 99%
“…In recent decades, a value-chain development (VCD) approach has been increasingly considered as one of the prominent paradigms in development thinking and practice that spur development of sustainable food systems, economic growth, and poverty reduction [3,4]. Awareness is also growing that gender equality and the development of sustainable value chains are interdependent goals [3,5].…”
Section: Introductionmentioning
confidence: 99%